Source Apportionment of Particulate Matter (PM10) and Indoor Dust in a University Building - Hafizan, Juahir; Jafon, Ng Mum Zhong; Mohd Talib, Latif (2014)
A study on source apportionment of indoor dust and particulate matter (PM10) composition was conducted in a university building by using chemometrics. The objective of this study was to investigate the potential sources of selected heavy metals and ionic species in PM10 and indoor dust. PM10 samples were collected using a low-volume sampler (LVS) and indoor dust was collected using a soft brush. Inductively coupled plasma spectrometry (ICP-MS) was used to determine the concentration of heavy metals, while the concentration of cations and anions was determined by atomic absorption spectrometer (AAS) and ion chromatography (IC), respectively. The concentration of PM10 recorded in the building throughout the sampling period ranged from 20 ± 10 μgm−3 to 80 ± 33 μgm−3. The composition of heavy metals in PM10 and indoor dust were dominated by zinc (Zn), followed by lead (Pb), copper (Cu), and cadmium (Cd). Principle component analysis (PCA) and multiple linear regression (MLR) showed that the main sources of pollutants in PM10 came from indoor renovations (73.83%), vehicle emissions (16.38%), earth crust sources (9.68%), and other outdoor sources (0.11%). For indoor dust, the pollutant source was mainly earth crust. This study suggests that chemometrics can be used for forensic investigation to determine the possible sources of indoor contaminants within a public building.